2013
DOI: 10.1016/j.repce.2012.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell therapy in heart disease

Abstract: Cardiovascular disease is among the main causes of mortality and morbidity worldwide. Despite significant advances in medical and interventional therapy, the prognosis of conditions such as ischemic heart disease is still dismal. There is thus a need to investigate new therapeutic tools, one of which is stem cell therapy. Hematopoietic stem cells are the most studied type, and the fact that their biology is relatively well understood has led to their being used in preclinical research and clinical trials. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The first clinical trial using cultured MSCs was carried out in 1995 on patients with hematologic malignancies . Since then, MSCs have been used for treatment of different diseases such as heart and cardiovascular, autoimmune, neurodegenerative, liver, diabetes, cancer and bone disease . Analyzing the literature, we showed that the most frequent usage of MSCs in clinical trial studies was on osteo‐diseases …”
Section: Introductionmentioning
confidence: 99%
“…The first clinical trial using cultured MSCs was carried out in 1995 on patients with hematologic malignancies . Since then, MSCs have been used for treatment of different diseases such as heart and cardiovascular, autoimmune, neurodegenerative, liver, diabetes, cancer and bone disease . Analyzing the literature, we showed that the most frequent usage of MSCs in clinical trial studies was on osteo‐diseases …”
Section: Introductionmentioning
confidence: 99%
“…In relation to decreased akinetic area, a decrease of 34% for cell therapy and 61% for group VEGF + Ang1, affirming the angiogenic potential and the potential decline in akinetic area of mesenchymal cells 22,25 , and promotes improvement in rates ejection fraction, diastolic and systolic diameter of the left ventricle.…”
Section: ■ Discussionmentioning
confidence: 72%
“…30 MSCs have shown helpful effects in CVDs, including myocardial infarction (MI), arrhythmias, coronary artery disease (CAD) and atherosclerosis. 31 Moreover, these cells exert paracrine effects such as neoangiogenesis, reducing myocardial fibrosis and remodeling. 32 The injection of cell-free medium containing the secreted factors of MSCs has improved myocardial regeneration after MI.…”
Section: Stem Cell Therapy In the Cardiovascular Systemmentioning
confidence: 99%